The temporal development of dust formation and destruction in nova sagittarii 2015#2 (V5668 SGR): a panchromatic study - Gehrz, Robert D.; Krautter, Joachim (The astrophysical journal, 2018)
We present 5-28 μm SOFIA FORECAST spectroscopy complemented by panchromatic X-ray through infrared observations of the CO nova V5668 Sgr documenting the formation and destruction of dust during ∼500 days following outburst. Dust condensation commenced by 82 days after outburst at a temperature of ∼1090 K. The condensation temperature indicates that the condensate was amorphous carbon. There was a gradual decrease of the grain size and dust mass during the recovery phase. Absolute parameter values given here are for an assumed distance of 1.2 kpc. We conclude that the maximum mass of dust produced was 1.2 × 10−7 M ⊙ if the dust was amorphous carbon. The average grain radius grew to a maximum of ∼2.9 μm at a temperature of ∼720 K around day 113 when the shell visual optical depth was τ v ∼ 5.4. Maximum grain growth was followed by a period of grain destruction. X-rays were detected with Swift from day 95 to beyond day 500. The Swift X-ray count rate due to the hot white dwarf peaked around day 220, when its spectrum was that of a kT = 35 eV blackbody. The temperature, together with the supersoft X-ray turn-on and turn-off times, suggests a white dwarf mass of ∼1.1 M ⊙. We show that the X-ray fluence was sufficient to destroy the dust. Our data show that the post-dust event X-ray brightening is not due to dust destruction, which certainly occurred, as the dust is optically thin to X-rays.
Gesehen am 11.12.2019